2020
DOI: 10.1111/jppi.12368
|View full text |Cite
|
Sign up to set email alerts
|

Same Progress for All? Inclusive Education, the United Nations Convention on the Rights of Persons With Disabilities and Students With Intellectual Disability in European Countries

Abstract: Over the course of the last 30 years, inclusive education has emerged as a key aim of education policies around the world. Also in Europe, most countries took efforts to make their education systems more inclusive—which led to growing numbers of children and young persons with disabilities in general education in Europe. The implementation processes of the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) fuelled these efforts. However, as some authors have argued, not all students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 30 publications
(35 reference statements)
0
26
0
Order By: Relevance
“…It is important to evaluate the effect of various inclusive and special education programs and settings on outcomes for children with learning or behavioral difficulties in order that a comprehensive review of the effectiveness of each of these can be provided. This involves examining outcomes for a range of educational options, such as those typically used in many countries [1,2]. A recent study of seven European countries [2] found that, although there was a trend toward increased inclusion of children with learning or behavioral difficulties in mainstream schools, most countries educate some children in four different types of settings, with a range of special education support.…”
Section: Evaluating the Effectiveness Of Inclusive And Special Education Programsmentioning
confidence: 99%
“…It is important to evaluate the effect of various inclusive and special education programs and settings on outcomes for children with learning or behavioral difficulties in order that a comprehensive review of the effectiveness of each of these can be provided. This involves examining outcomes for a range of educational options, such as those typically used in many countries [1,2]. A recent study of seven European countries [2] found that, although there was a trend toward increased inclusion of children with learning or behavioral difficulties in mainstream schools, most countries educate some children in four different types of settings, with a range of special education support.…”
Section: Evaluating the Effectiveness Of Inclusive And Special Education Programsmentioning
confidence: 99%
“…It is a practice targeted exclusively at students with special educational needs (SEN), based on the components of special needs education. Specialised schools are recognised as a Social "displacement" (social and cultural grounds) L. Vygotsky (1993) Disability, disordered function (biological grounds) L. Vygotsky (1993) more appropriate environment for the education of students with special educational needs (Buchner et al, 2021). The competency of the pedagogues is linked to special needs education.…”
Section: Inclusive Special Needs Educationmentioning
confidence: 99%
“…However, when pursuing an inclusive and quality implementation of inclusion for all, it is obligatory to find solutions for students with mental disorders, most of whom still attend specialised schools (Buchner et al, 2021), principles of joint operation of specialists and teachers in building a flexible learning environment (Takala et al, 2009), and to eliminate obstacles for equal participation of all students (Ramberg & Watkins, 2020).…”
Section: Inclusion For Allmentioning
confidence: 99%
“…Moreover, the rates of students with special needs (SEN) in mainstream secondary schools are lower than in primary schools, despite the gap between the percentage of students with SEN in mainstream primary and secondary schools has reduced in recent years (Buchner et al, 2021 ). Mastropieri and Scruggs ( 2001 ) remarked, two decades ago, the complexities of inclusion in secondary education, ranging from academic complexity, pace of instruction and teacher attitudes.…”
Section: Introductionmentioning
confidence: 99%